Prediabetes awareness among different specialities of physicians: A review - Mohsina Hyder K, Viswanathan Balasubrmaniam, Rajanandh MG, Sivasankaran Ponnusankar (Journal of Applied Pharmaceutical Science, 2022)
The purpose of this review is to assess the knowledge, attitude, and practice on prediabetes among the different specialities of physicians, especially general practitioners, endocrinologists, non-endocrine specialists, diabetologists, and residents from different countries. All the articles on physicians’ prediabetes awareness measured using questionnaires were searched and relevant articles among them were used in the preparation of this review. Some results showed an inverse correlation between the level of knowledge and years of experience. Even though practitioners were aware of prediabetes, majority of the general practitioners did not screen the high-risk population, especially in India. Only about one-third of the participants knew the American Diabetes Association (ADA) directions for starting metformin. However, endocrinologists and diabetologists showed the highest level of knowledge of prediabetes compared to general practitioners and non-endocrine specialists. Moreover, younger physicians showed better knowledge regarding numerical values related to prediabetes criteria, while most of the senior physicians did not follow the current prediabetes guidelines. The results suggest an urgent need to widely implement prediabetes education in medical schools and in continuing medical education programs among practicing physicians.
Keywords: Prediabetes, prediabetes questionnaire, physician awareness, diabetes prevention programs, prediabetes awareness, prediabetes knowledge, attitude, practice